Entrepreneurial finance: financing antecedents and SMEs performance - Maria Rio Rita; Sugeng Wahyudi (Journal of Economics, Business, and Accountancy Ventura, 2018)
Various previous research has been conducted on the relationship between a cognitive bias and financing decisions by entrepreneurs. Besides that, it still needs to be examined whether a cognitive bias is related with SMEs performance through company finances. The purpose of this research is to test financing antecedents and SMEs performance. One kind of a creative industry, batik SMEs that are located in Pekalongan, Central Java, Indonesia, are the object of this research. There were 190 respondents chosen from batik entrepreneurs. The holistic testing of this empirical model used structural equation modelling (SEM) with an AMOS program. The research results found that an entrepreneur’s cognitive bias has a significant positive bias towards financing. Meanwhile, entrepreneurial orientation and financing also are proven to have a significant positive influence towards SMEs performance. No entrepreneurial orientation influence was discovered towards SMEs performance. Furthermore, the output analysis revealed there is an indication of a strong relationship between a cognitive bias and entrepreneurial orientation. Therefore, this model can be revised, developed, and retested by considering the agenda of this research to enrich insights in the entrepreneurial finance sphere.